Metabolic alterations in non-alcoholic fatty liver disease (NAFLD): consequences of AGXT downregulation on glyoxylate detoxification - Gianmoena, Kathrin (Technische Universität Dortmund, 2017)
Non-alcoholic fatty liver disease (NAFLD) encompasses a wide range of liver diseases, where excessive hepatic lipid accumulation is a common factor. It is highly prevalent worldwide, and is associated with an elevated risk of developing more severe liver diseases, as well as cardiovascular and renal diseases, such as the formation of kidney stones. The aim of this study was to identify and investigate lipid-associated metabolic and functional alterations in steatotic livers and hepatocytes. For this purpose, a mouse model of NAFLD, the leptin deficient ob/ob mouse, was implemented and its steatotic phenotype investigated. In vitro induction of steatosis was established in HepG2 cells and in primary mouse hepatocytes to more directly study the consequences of lipid accumulation. Macrovesicular steatosis was confirmed in the hepatocytes of ob/ob mice as well as in the in vitro steatosis model, and was manifested by the displacement of nuclei towards the periphery and by a perturbed autophagy flux, thus recapitulating features of human NAFLD. To estimate the impact of hepatic lipid accumulation on global gene expression across species, hepatic genome-wide expression data of human NAFLD, of the leptin deficient ob/ob mouse model, and of lipid-loaded HepG2 cells were compared. Here, 22 deregulated genes in mouse and human NAFLD, as well as in the in vitro model of lipid accumulation were identified. Among the 22 genes, the liver specific AGXT gene, encoding the alanine-glyoxylate aminotransferase (AGXT), was found to be downregulated. The enzyme AGXT is essential for the detoxification of glyoxylate to glycine in order to prevent the formation of oxalate, a factor that increases the predisposition to developing kidney stones. For this reason, further steps focused on exploring the downregulation of AGXT upon fatty liver as the molecular mechanism underlying the increased risk of kidney stones in patients with NAFLD. The steatosis-associated repression of AGXT was validated in a small, independent collection of primary human hepatocytes, in a Western diet-induced mouse model of NAFLD, and in the in vitro steatosis model of primary mouse hepatocytes, as well as in an additional hepatic cell line. In the leptin deficient ob/ob mouse model, the repression of Agxt was accompanied by a reduced hepatic glycine concentration and by a slightly increased urinary oxalate excretion. These observations implied physiological consequences of the decreased expression of Agxt due to the reduced glyoxylate detoxification capacity in this mouse model of NAFLD. Moreover, cultivated ob/ob hepatocytes produced more oxalate upon treatment with the glyoxylate precursor hydroxyproline compared to the ob/+ hepatocytes, and thus suggested an increased susceptibility towards hydroxyproline levels in steatosis. The downregulation of AGXT in fatty liver was associated with hypermethylation of its promotor in steatotic primary human and murine hepatocytes. This indicated a possible methylation-dependent regulation of AGXT expression in vivo. The in vitro model of steatosis was not able to recapitulate this feature, suggesting alternative mechanisms of transcriptional downregulation of AGXT. Altogether, the present study describes the hepatic steatosis-dependent deregulation of the glyoxylate detoxification pathway via AGXT repression. It could demonstrate that the lipid-dependent downregulation of AGXT in hepatocytes can result in increased generation of oxalate, and thus susceptibility for renal calcium oxalate deposits. It is the first known report, identifying the downregulation of AGXT as a missing molecular link between fatty liver and the increased risk of kidney stones in patients with NAFLD.
Keywords: NAFLD; Gene array; AGXT; Glyoxylate metabolism; 570; 540